2022
DOI: 10.18857/jkpt.2022.34.5.218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insole to Flexible Flat Foot on Dynamic Balance and Ankle Muscle Activity during the Y-Balance Test

Abstract: Purpose: This study sought to identify the effects of an insole applied for the flexible flat-foot condition on dynamic balance and ankle muscle activities during the Y-balance test (YBT). Methods: Thirteen flexible flat-footed adults and an equal number of normal-footed adults were enrolled. The dynamic balance of the subjects was measured using the YBT, which is a reach test. While they were reaching forward with their foot, the percentage maximum voluntary isometric contraction (MVIC) of the tibialis anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…Although the short-term use of FOs has shown immediate improvements in balance [10][11][12], long-term results are mixed, with some studies reporting benefits after approximately 4 weeks of use [5,14], while others found no significant effects, especially when compared to other interventions [5,[13][14][15]. Despite the potential of FOs to enhance kinesthetic awareness and improve balance, the efficacy of this intervention remains a topic of ongoing debate [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although the short-term use of FOs has shown immediate improvements in balance [10][11][12], long-term results are mixed, with some studies reporting benefits after approximately 4 weeks of use [5,14], while others found no significant effects, especially when compared to other interventions [5,[13][14][15]. Despite the potential of FOs to enhance kinesthetic awareness and improve balance, the efficacy of this intervention remains a topic of ongoing debate [9,16,17].…”
Section: Introductionmentioning
confidence: 99%